Biological differences between reflux stimulated proliferative stomal lesions and N-methyl-N '-nitro-N-nitrosoguanidine induced carcinomas in Wistar rats. - Rodrigues, MAM; Kobayasi, Shoiti [UNESP]; Naresse, Luiz Eduardo [UNESP]; Leite, CVD; Nakanishi, H.; Imai, T.; Tatematsu, M. (Elsevier B.V., 1999)
The morphology and evolution of epithelial lesions that developed at a gastrojejunal stoma due to reflux of duodenal contents were compared with MNNG-induced carcinomas in the pyloric mucosa of rats in a long term experiment. Random bred male Wistar rats were given MNNG in drinking water (100 mg/l) for 12 weeks and then one group was submitted to a gastrojejunal anastomosis at the greater curvature in the oxyntic mucosa, Untreated rats underwent either gastrojejunostomy or gastrotomy. The animals were killed at the 24th and 66th weeks of the experiment. The lesions obtained in the pyloric mucosa and in the mucosa of the gastrojejunal stoma were analyzed histologically using hematoxylin and eosin staining and immunohistochemistry for pepsinogen isoenzyme 1. Duodenal reflux induced proliferative lesions at the gastrojejunal junction that increased in incidence and size with time. Histologically they consisted of benign epithelial proliferation of gastric type. No evidence of malignant transformation within the gastric components of the proliferative lesions at the gastrojejunal stoma was observed even at the 66th week, Adenocarcinomas induced by MNNG in the pyloric mucosa increased in size during the experiment and were morphologically and histochemically distinct from the proliferative lesions at the gastrojejunal junction. In conclusion, proliferative lesions at the gastrojejunal stoma stimulated by duodenal reflux are biologically distinct from adenocarcinomas induced by MNNG in the pyloric mucosa. They do not seem to be precursor lesions of gastric carcinogenesis, as they do not undergo malignant transformation even after long-term, up to 66 weeks, follow-up. (C) 1999 Elsevier B.V. Ireland Ltd. All rights reserved.
Keywords: stomal lesions; duodenal reflux; morphology of tumors; N-methyl-N '-nitro-N-nitrosoguanidine; rat gastric carcinogenesis